A Survey on Vulnerabilities, Attacks and Issues in MANET, WSN and VANET - Yogapriya, R; Subramani, A (International Journal of Computer Sciences and Engineering, 2025)
An attack in computers systems and its networks may attempt to explore, disable, destroy, steal or gain unauthorized access to make illegal use of asset. World Economic Forum has observed that Scalable algorithms and Robustness of cyber-attacks have significant improvement in the technology. Recent technical reports stated that offensive cyber capabilities were developed more rapidly than our ability to deal with hostile incidents. A computer network attack disrupts the integrity or authenticity of data, usually through malicious code that alters program logic that controls data, leading to errors in output. Network security covers a wide variety of both public and private networks that are regularly utilized in jobs like, transactions and communications among businesses, government agencies and individuals. The review paper presents about the types of attacks with issues and challenges in MANET, WSN and VANET.